An Analysis of Teachers’ Questioning Strategies during the Classroom Interaction at the VIII Grade of SMP Negeri 1 Gunungsitoli Utara - Revita Niskar Zalukhu; Trisman Harefa; Elwin Piarawan Zebua; Riswan Zega (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to reveal the application of questioning strategies by English teachers in class VIII of SMP Negeri 1 Gunungsitoli Utara and students' responses to these strategies. The research method used a descriptive qualitative approach with a case study method. The research took place from November to February 2024 in class VIII of SMP Negeri 1 Gunungsitoli Utara. The research informants consisted of two English teachers and five grade VIII students. Data were collected through observation, interview, and documentation. The data were analyzed using qualitative analysis technique which includes data collection, data reduction, data presentation, and conclusion drawing/verification. The results showed that English teachers had implemented various questioning strategies, such as Display Questions, Referential Questions, and Procedural Questions. However, the Simplification and Inquiry strategies still need to be improved. Students' responses showed enthusiasm and interest in the lessons, but also confusion and fear when answering in English, caused by limited vocabulary and fear of being wrong. Although the questioning strategy aimed to improve students' English and critical thinking skills, these barriers reduced students' courage to actively participate. Further support is needed for teachers in developing more effective and comprehensive questioning strategies.